2018
DOI: 10.1002/ptr.6242
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective activity of praecoxin A isolated from Melaleuca ericifolia against carbon tetrachloride‐induced hepatotoxicity in mice. Impact on oxidative stress, inflammation, and apoptosis

Abstract: The hepatoprotective activity of praecoxin A, an ellagitannin from Melaleuca ericifolia, was determined against CCl 4 -induced toxicity in mice. Praecoxin A was administered (25, 50, and 100 mg/kg) for 5 days followed by CCl 4 . Praecoxin A markedly ameliorated the CCl 4 -induced increase in AST (by 19, 52, and 56%), ALP (22, 45, and 48%), ALT (11, 47, and 54%), total bilirubin (14, 27, and 28%), and MDA (26, 44, and 51%) at the tested doses, respectively, as compared with CCl 4 group. It was evident that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 29 publications
(44 reference statements)
1
4
0
Order By: Relevance
“…15,18 Al-Sayed et al reported that CCL 4 increased MDA levels and caspase-3 expression. 38 Similarly, in the present study, we observed that CCL 4 increased MDA levels and caspase-3 expression in enterocytes.…”
Section: Discussionsupporting
confidence: 84%
“…15,18 Al-Sayed et al reported that CCL 4 increased MDA levels and caspase-3 expression. 38 Similarly, in the present study, we observed that CCL 4 increased MDA levels and caspase-3 expression in enterocytes.…”
Section: Discussionsupporting
confidence: 84%
“…Reduction of non-enzymatic antioxidant GSH in neuronal and hepatic cells following sub-acute oral administration of unripe fruit extract of Blighia sapida could be a consequence of increased utilization for trapping free radicals. Depletion of GSH in the liver correspondingly affects the glutathione system in interrupting lipid peroxidation chain reaction [58,59]. The result from this study thereby establishes that unripe Blighia sapida fruit induces oxidative stress.…”
Section: Discussionmentioning
confidence: 65%
“…Acute liver injury induced by CCl 4 is associated with the activation of inflammatory processes, oxidative stress, and apoptosis (Al‐Sayed et al, 2019 ; Sun et al, 2022 ). In general, treatment with NWE, NPE, and hypaphorine all showed liver protective effects, as evidenced by data from the histopathological evaluation (liver injury score) and the blood chemical assays (ALT and AST level) (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%